Efektifitas Ektrak Ikan Gabus Terhadap Penyembuhan Luka Perineum Di Rumah Sakit Permata Hati Cikupa Tangerang Tahun 2024 - Ita Septiani; Wiwin Widyastuti (Jurnal Ners, 2025)
Perineal wounds are a type of tear that occurs in the perineum during childbirth. The perineum is the area between the vagina and the anus in women. Perineal tears often occur during labor, especially when the baby is born and the baby's head passes through the birth canal.To find out the effectiveness of snakehead fish extract on the healing of perineal wounds in hospitals Permata Hati Cikupa Tangerang in 2024.This study is an experimental Quasy research with a group of snakehead fish. The independent variable in this study was the feeding of snakehead fish, the dependent variable was the duration of healing of perineal wounds. The total number of respondents in this study was 10 respondents based on data from postpartum mothers who experienced perineal injuries which were divided into two groups, namely 5 respondents in the group who were given snakehead fish, 5 respondents in the group who were not given snakehead fish which were taken by puposive sampling. Data analysis was carried out univariate and bivariate, to determine the effectiveness of snakehead fish on the healing time of perineal wounds using an independent sample test if it is normally distributed and if it is not normally distributed, use the Mann-Whitney test of SPSS versii 25.The researcher's assumption is that after a study was conducted at Permata Hati Cikupa Hospital in Tangerang in 2024 with the administration of snakehead fish extract on the healing of perineal wounds for 7 days, as much as 200 grams must be consumed every day. The author also conducted an evaluation and made a comparison between the theory and the existing case, the author concluded that there was no difference between the theory and the case, the stitches seemed dry and had been tight on the seventh day.Consumption of snakehead fish or snakehead fish extract has been proven to be effective in accelerating the healing process of perineal wounds in postpartum mothers and has benefits, namely it can reduce homocysteine levels in the blood, prevent heart disease and stroke and can improve children's intelligence and health, and recommends consuming snakehead fish or snakehead fish extract to accelerate the healing of perineal wounds.